(untitled) (LACCEI, 2024)
Given the recurring extreme rains and the increase in river flow in many basins on the Pacific slope, the Peruvian government is considering building river defenses to prevent future floods and overflows. One of the most affected basins is that of the Mala River, which suffered the overflow of the waters of its main channel in March 2017, causing serious economic and material damage. Doing an exploration in the basin, it was found that there is a hydrometric station in the main channel of the Mala River called La Capilla, which has valid daily records between the years 2018 - 2020. Unfortunately, this number of records is insufficient for any study. hydrological. It is for this reason that the purpose of this research was to be able to generate daily historical flow records based on the ERA5 gridded climate information of satellite origin. These data were used in the French GR4j model, obtaining excellent R2 correlation values in its calibration, validation and data extension, which allowed us to generate a flow record at daily flow between the years 1980 and 2020. These records will be useful for future projects against future overflows of the Mala River.